Pemberdayaan Ekonomi Masyarakat Upaya Membangun Ketahanan Diri di Era Pandemi - Fithrotin, Fithrotin; Lathifah, Eny (Proceedings of Annual Conference on Community Engagement, 2022)
In 2020 WHO has declared the Corona virus outbreak (COVID-19) as a pandemic. In human history, COVID-19 has become a global disease that has spread to various countries. This outbreak is relatively new because it has never happened before. The COVID-19 pandemic not only had an impact on physical health but also mental health. The society is faced with significant changes in the social life such as social restrictions, cutting the number of employees, the obligation to work from home, abd teaching children online schools. These various things are the causes of many people experiencing mental health problems such as increased anxiety and stress which have an effect on unproductive behavior. Not only that, many people are forced to adapt to a new reality that is dominated by fear of the spread and transmission of the virus. Therefore, the ability of resilience as a mechanism of self-defense to survive in the midst of the current global pandemic conditions needs to be improved one of them with assistance in social religious institutions based on islamic phylantrophy. The purpose of the assistance is the community can manage themselves to remain calm and focused in dealing with and solving problems, being able to solve their problems and get through the toughest conditions, to identify the causes of the problems they face. The method used by PAR is a process of seeking the development of practical knowledge in understanding social, political, environmental, or economic conditions. PAR is also a participatory research and development method that recognizes social relationships and the value of the reality of our experiences, thoughts and feelings. Outcomes of assistance in the community are emotional regulation, impulse control, optimistic attitude, self-efficacy, and increase in positive aspects.